Factors Influencing the Pedagogical Competence of Elementary School Teachers in the Digital Era: A Survey Study - Babang Robandi; Wawan Setiawardani; Ade Apriyanto (Journal of General Education and Humanities, 2025)
This study aims to explore the factors influencing the pedagogical competence of elementary school teachers in the digital era. The integration of digital technology into education faces challenges due to gaps in teachers’ pedagogical competence, which are shaped by disparities in infrastructure, digital literacy, access to professional development, policy support, and teacher attitudes and motivation. Employing a survey research design, this study involved 270 elementary school teachers from West Java Province as participants. Data were collected through a validated online questionnaire, with an Aiken’s validity index above 0.8 and a Cronbach’s Alpha reliability estimate of 0.867. Descriptive statistics and qualitative analysis using the Miles and Huberman model were utilized to examine the factors affecting teachers’ pedagogical competence. The results reveal significant disparities in ICT device availability, low digital literacy, limited access to training, weak school policy support, and psychological barriers that hinder ICT integration. Although 73% of teachers believe ICT improves learning outcomes, 54.07% remain hesitant to experiment due to fear of failure. These findings underscore the need for holistic training programs, infrastructure improvements, inclusive policies, and peer learning-based mentoring to strengthen teachers’ pedagogical competence in the digital era.